Answer:
3
Step-by-step explanation:
x-y^2
Let x = 12 y=3
12 - (3)^2
12 -9
3
Answer:
7.071 cm
Step-by-step explanation:
Left 3 because the 3 is in the parenthesis
-7 + 10 = 3
=
10 + (-7)
Is the same as
10 - 8
…
Not sure if this was that helpful.. I hope it did.
P = 5 .............................................
this is how=
first you expand the second equation
<span>25 + 4p = -18 + -12 + 6p + 9p
</span>
then you add the like terms in the second equation:
25 + 4p = -30 + 15p
then this is how=
25+30 = 15p -4p
55=11p
p= 5